Growth performance and quality traits of siberian sturgeon (A. baerii) juveniles fed diets including Nannochloropsis gaditana and Scenedesmus almeriensis microalgae meal - T. Bongiorno; A. Di Biase; M. Vasconi; V. M. Moretti; A. Lopez; A. Tava; D. Carminati; G. D'Imporzano; M. Montedoro; F. Adani; F. G. Acién Fernández; F. J. Alarcón; et al. (2019)
The demand for aquafeed grown exponentially in the last decade and is expected to increase further in the coming years (FAO 2018). The wild fish used for the fish meal and oil, currently used in feed formulated for carnivorous species, will be used in human consumption and less available for aquaculture. Among the potential ingredients of future use in aquafeed, microalgae represent a promising matrix, as characterized by nutritional, nutraceuticals and immunostimulant properties ( Camacho-Rodríguez et al., 2017) . However the high production cost is a limiting factor for their use. The development of a microalgae-based biorefinery, able to use some by-products and agro-industrial waste to produce biomass would enable to limit the disposal costs sustained by the companies and to lower the production costs of the microalgae. The present research was undertaken to evaluate effect on growth response and fillet quality traits of sturgeon ( A. baerii) fed with two microalgae freeze-dried biomass Nannochloropsis gaditana and Scenedesmus almeriensis grown in Sinthetic Medium (SM) or in diluted Pig Manure (PM) and included in partial substitution of dietary fish meal and oil. Materials and methods Four complete diets were formulated to be grossly iso-proteic and iso-lipidic . A control diet (C ) was prepared using a blend of conventional animal and vegetal protein sources. The test diets coined respectively N. gaditana grown o n Synthetic Medium (NSM ), N. gaditana growno in pig manure (NPM), S. almeriensis grown on Synthetic Medium (SSM) and S. almeriensis grown on Pig Manure (SPM) were prepared by replacing the 10% of protein and lipid supplied by the blend of conventional protein and lipid-rich ingredients with microalgae . All the ingredients are mixed and pelleted by a cold extrusion process (70°C). Each diet were randomly assigned to tank and tested in triplicate according to a monofactorial design. Microalgae dried biomass and diets were analized microbiologically and verified for nutritional quality. To carried ...